Synthesis of Magnetic Chitosan Composite Beads as an Adsorbent for Removal of Organic Matter from Peat Water - Uul Warosatul Ambiya; Nurlina Nurlina; Gusrizal Gusrizal (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Groundwater in peatlands has the potential to be utilized as a water source, but its high organic matter content presents challenges. This study aimed to improve the quality of peat water through the adsorption of organic matter using chitosan magnetic beads composite adsorbent. Magnetic chitosan beads (KMB) composite was synthesized by mixing chitosan, acetic acid, and a mixture of Fe2+/Fe3+ solution with a mole ratio of 1:2. This mixture was then dropped into a sodium hydroxide solution. In addition to KMB, magnetic composite beads containing glutaraldehyde crosslinking agent (KMBG) were also synthesized. The results of composites analysis using a Fourier transform infrared (FTIR) spectrophotometer showed typical Fe-O absorption bands at 582 cm-1 and 578 cm-1 for KMB and KMBG. The typical C=N absorption band for glutaraldehyde in KMBG appeared at 1631 cm-1. X-ray diffraction (XRD) analysis revealed the characteristic peaks of Fe3O4 for KMB and KMBG at 2θ = 30.2°, 35.5°, 43.2°, 57.0°, and 62.8° with an amorphous structure. The adsorption of organic matter was performed by varying the pH (2, 3, 4, and 5) of peat water and the mass of the adsorbent (50, 70, 100, 200, and 300 mg). The optimum adsorption occurred at pH 2 with an absorbent mass of 0.1 g KMB and 0.07 g KMBG. Applying KMB on peat water reduces turbidity, color, and absorbance at a wavelength of 254 nm (Aλ=254), which is better than using KMBG. These three parameters’ efficiency percentages were 44%, 78%, and 74% for KMB and 17%, 30%, and 59% for KMBG.